Pelatihan Cara Penanaman Tanaman Obat Keluarga (Toga) Bersama (KWT) dan (PKK) di Desa Karya Maju A1 - Nugroho Notosutanto Arhon Dhony; Dea Husnul Khotimah; Alvini Agustin; Novi Lesiana; Vira Rafelinda; Bayu Irawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Family Medicinal Plants (TOGA) are plants that are used to describe maintenance and cultivation reports that are used as treatment. The training was carried out in Karya Maju A1 Village, which is a village in Keluang District, Musi Banyuasin Regency, whose main livelihoods are gardening and farming. TOGA is a herbal plant for medicines, for example, lime, turmeric, betel, brotowali and others. other. Therefore, holding training on how to plant family medicinal plants (TOGA), carried out and directed by Students of the PGRI Palembang University Real Work Lecture (KKN) to improve the skills and creativity of the Karya Maju A1 village community, Members of the Women Farmers Group (KWT), members (PKK). The method used is how to cultivate family medicinal plants using lecture, discussion, and question and answer methods. The aim of this training is to find out how the Training on How to Grow Medicinal Plants in the Family (TOGA) is carried out.